BIOCONVERSION OF AGRICULTURAL BY-PRODUCTS TO ALGINATE BY AZOTOBACTER VINELANDII AND PHYSICO-CHEMICAL OPTIMIZATION FOR HYPER-PRODUCTION - S. Saeed; A. S. Hashmi; Ikram-ul-Haq; M. Tayyab; A. R. Awan; A. A. Anjum; S. Firyal (Journal of Animal and Plant Sciences, 2016)
Alginate, a biopolymer of industrial interest is commercially extracted from marine brown algae. Due to variation in composition from different species, there is rising interest in bacterial alginate. The present study was designed to assess the feasibility of using different agro-industrial wastes like wheat bran, rice polishing and cane molasses for alginateproduction by Azotobacter vinelandii. Optimization of basal media composition and various physical parameters was also done. On fermentation of 7.5% (w/v) wheat bran maximum alginate production was reported at 48 hours of incubation time with 6% (v/v) inoculum size at pH 7.0, 300C and agitation speed of 200 rpm. Addition of different optimum levels of ionic salts i.e. 1.5% CaCl2 and 2% MgSO4. 7H2O gave significantly higher quantity of alginate whereas KH2PO4 and NaCl reduced the yield of alginate. Among different nitrogen sources tested, 2% corn steep liquor showed significantly higher yield of alginate (7.46 g/L). Alginate produced was found to be 98% pure by HPLC method. The present exploration depicted that alginate can be efficiently produced utilizing cheap agricultural wastes to save the foreign exchange.
Keywords: Alginate; Azotobacter vinelandii; Agricultural by-products; fermentation